Design of a Rice Rope Laying Machine for Direct Sowing - LV, Xiao-Lian; LV, Xiao-Rong; MA, Rong-Chao (Engineering Transactions, 2017)
The research and development of a rice rope laying machine (RRLM) provides new ideas for a design of a rice direct seeding machine, and solves existing problems encountered in direct seeding techniques currently in use. The RRLM has been developed based on an in-depth analysis of the design principles and main structure parameters of rice direct seeding machines. The completed machine consists of all necessary components including an anti-blocking device, sowing device, opening device, banking device, compacting device, etc. The optimal design of the parts and structure of the RRLM was completed using the three-dimensional Unigraphics NX (UG NX) software. The rationale and the performance of the machine and its components were analyzed using this virtual prototyping technology. The key technology problems commonly encountered, which included the opener being easily plugged up, the difficulty in adjusting/controlling the number of seeds per hole, and seeding rope easily broking during the process of laying, have all been effectively solved. The field test results have shown that this machine has the advantage of good maneuverability and high working efficiency, the reliability and quality of seeding rope placement meets (fulfills) the design requirements, the profiling and compacting effect of the machine is very good, and the uniformity of seeding depth and accurate rope placement are guaranteed.